A Census chronicle – reflections on the campaign for a religion question in the 2001 Census for England and Wales - Sherif, Jamil (Journal of beliefs and values, 2011)
The campaign from 1996-2000 to include the religion question in the 2001 Census for England and Wales was a defining event for Muslim communities in Britain because it provided formal recognition of their collective identity as a faith group, rather than being subsumed in the ‘black’, ‘Asian’ or ‘Pakistani/Bangladeshi’ ethnic categorisations of the past. A ‘micro‐history’ of this four‐year journey deserves to be put on the record, and this account provides a perspective from the point of view of one community advocacy body that had an active involvement, the Muslim Council of Britain (MCB). The account also draws on documents obtained under the Freedom of Information Act from the Office for National Statistics (ONS), the government department responsible for the Census. It describes the emergence of an interfaith alliance as a political pressure group and the civil servants' responses when faced with demands for change. A major social policy decision was eventually taken, not just through a process of rational negotiation, but through fortuitous and unscripted interventions of persons of goodwill. The campaign offered British Muslims their first comprehensive engagement with the variety of formal and informal networks, centres of power, institutions and processes that interact in the shaping of policy in a participative democracy.